2016
DOI: 10.1039/c5sc03677a
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer metallohelices: nanomolar potency and high selectivity

Abstract: New optically pure helicate-like architectures are extremely active against cancer cell lines, with IC50 values as low as 40 nM, but nearly three orders of magnitude less active against healthy cells. There is also low toxicity to microbes and amoeba.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 44 publications
2
40
1
1
Order By: Relevance
“…In addition, the Annexin V-FITC/PI double-labeled flow cytometry analysis revealed that the apoptotic rates of U2OS and 143B cells concentration-dependently increased with cinobufagin treatment. In consistent with our results, previous literature reports have shown that cinobufagin induces apoptosis in a variety of human tumor cells [9, 10, 12, 13, 15, 16]. Thus, these data indicate that the induction of apoptosis is the main cause of the tumor cell growth inhibition by cinobufagin.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the Annexin V-FITC/PI double-labeled flow cytometry analysis revealed that the apoptotic rates of U2OS and 143B cells concentration-dependently increased with cinobufagin treatment. In consistent with our results, previous literature reports have shown that cinobufagin induces apoptosis in a variety of human tumor cells [9, 10, 12, 13, 15, 16]. Thus, these data indicate that the induction of apoptosis is the main cause of the tumor cell growth inhibition by cinobufagin.…”
Section: Discussionsupporting
confidence: 93%
“…[5][6][7] In particular,h elicates have been shown to be potential drugs for cancer treatment. [8,9] Their anticancer properties result from their intrinsic chiral nature and topological features (size and charge), whichallow the specific recognition of DNA and noncovalentb inding. Pioneering studies of Hannon demonstrated that helicate complexes interactw ith DNA in new and distinctive ways, where the external surfaces of the heli-cates recognize unusualD NA junction structures, and induce remarkable intramolecular DNA coilinge ffects.…”
Section: Introductionmentioning
confidence: 99%
“…from achiral bis‐bidendate building blocks, and trinuclear triple‐stranded homo‐ and heterometallic helicates were reported by Ghosh and co‐workers . Metallohelices exhibiting anticancer activity with nanomolar potency were reported by Kaner et al . We have explored the coordination behavior of metal ions with heterocyclic nucleobases to synthesize complex supramolecular motifs with interesting photophysical properties such as fluorescent gold nanoclusters for cell nuclei imaging and luminescent silver complexes …”
Section: Figurementioning
confidence: 98%